A Band of Colours: Spectral Assemblies. (6th July 2022) - Karlsson, Ulrika
Abstract: Since scanners became a common tool in architecture schools around ten years ago, the tendency has been to record what is there in the built environment in an attempt to discover the interrelationships between spaces obscured by the materiality of building. However, architects are now starting to speculate using these new technologies. Founding member of architecture firms Brrum and servo stockholm, and Professor of Architecture at the KTH School of Architecture, Stockholm, Ulrika Karlsson investigates this through the work conducted by Michael Young, co‐founder of New York‐based practice Young & Ayata.